Water Use and Biomass Production in Tree Seedlings Irrigated Near Field Capacity in Arid Environment - Singh, G.; Rathod, T. R. (Indian Forester, 2012)
Soil water depletion in forty-five months old plants of E. camaldulensis, A. nilotica and D. sissoo was monitored in non-weighing 3 type of lysimeters of 2m Ã—2m Ã—2 m (8m3 capacity). Soil water was allowed to deplete up to 7.56% and was maintained at field capacity of Soil Water Content (SWC) by re-irrigating the seedlings at 36.2 mm. Total depletion of soil water from the plantation of E. camalulensis was 4.75mm day-1 m-1 depth. The depletion from A. nilotica plot was 3.45 mm day- and that of D. sissoo was 2.62 mm day-1. This indicated 13, 9 and 7 irrigation in 99, 94 and 97 days in E. camaldulensis, A. nilotica and D. sissoo plots, respectively. Partitioning between transpiration and evaporation was 66% and 34% in E. camaldulensis plot, 54% and 46% in A. nilotica plot and 38 and 62% in D. sissoo plots. The depletion in soil water from bare soil was 7.0 lit day that contribute significant amount of water loss. A provision of simple surface mulching with locally available under-shrubs and grasses saved the loss of 0.15 mm day (1.5 tones water ha-1day-1).